Effect of different seat position on lower limb kinematics, kinetic and electromyography during cycling - Chen, C.-H.; Lee, Y.-S.; Tsai, W.-C.; Hsieh, C.-H.; Chang, Y.-H.; Shiang, T.-Y. (Journal of Science and Cycling, 2019)
Background: An accurate riding position can not only attenuate injuries, but also enhance performance. However, which adjustment could provide better performance improvement is still arguable. The main factor that leads to poor position can be attributed to inaccurate saddle position. Unquestioningly, saddle position is the crucial adjustment. Generally, seat tubes on road bike are tilted-design, that is, when the saddle being adjusted, the saddle height and forward- backward position will differ simultaneously.